(untitled) (Fiep Bulletin - online, 2015)
The objective of this article is to discuss manifestations of risk and dizziness experienced during underwater fishing, using accounts presented by enthusiasts. Risk and dizziness cause sensations of pleasure in underwater fisherman during and after conducting their activities. These men of action seek to prepare themselves beforehand in order to minimize the risks and to control their state of mind, with the intent of being able to transit on the threshold of safety, in this way seeking, through underwater fishing, pleasure which allows them to live intensely.